Co-Exposure to Aristolochic Acids I and II Increases DNA Adduct Formation Responsible for Aristolochic Acid I-Mediated Carcinogenicity in Rats - Bárta, František; Dedíková, Alena; Bebová, Michaela; Dušková, Šárka; Mráz, Jaroslav; Schmeiser, Heinz H; Arlt, Volker M; Hodek, Petr; Stiborová, Marie (International journal of molecular sciences, 2021)
The plant extract aristolochic acid (AA), containing aristolochic acids I (AAI) and II (AAII) as major components, causes aristolochic acid nephropathy (AAN) and Balkan endemic nephropathy (BEN), unique renal diseases associated with upper urothelial cancer. Recently (Chemical Research in Toxicology 33(11), 2804-2818, 2020), we showed that the in vivo metabolism of AAI and AAII in Wistar rats is influenced by their co-exposure (i.e., AAI/AAII mixture). Using the same rat model, we investigated how exposure to the AAI/AAII mixture can influence AAI and AAII DNA adduct formation (i.e., AA-mediated genotoxicity). Using 32P-postlabelling, we found that AA-DNA adduct formation was increased in the livers and kidneys of rats treated with AAI/AAII mixture compared to rats treated with AAI or AAII alone. Measuring the activity of enzymes involved in AA metabolism, we showed that enhanced AA-DNA adduct formation might be caused partially by both decreased AAI detoxification as a result of hepatic CYP2C11 inhibition during treatment with AAI/AAII mixture and by hepatic or renal NQO1 induction, the key enzyme predominantly activating AA to DNA adducts. Moreover, our results indicate that AAII might act as an inhibitor of AAI detoxification in vivo. Consequently, higher amounts of AAI might remain in liver and kidney tissues, which can be reductively activated, resulting in enhanced AAI DNA adduct formation. Collectively, these results indicate that AAII present in the plant extract AA enhances the genotoxic properties of AAI (i.e., AAI DNA adduct formation). As patients suffering from AAN and BEN are always exposed to the plant extract (i.e., AAI/AAII mixture), our findings are crucial to better understanding host factors critical for AAN- and BEN-associated urothelial malignancy.
Keywords: adukty DNA; Male; DNA adducts; Rats, Wistar; NAD(P)H:quinone oxidoreductase 1; genotoxicity; aristolochic acid II; cytochrome P450; DNA nádorová; aristolochic acid I; mužské pohlaví; potkani Wistar; aristolochic acid nephropathy; aristolochic acid-mediated carcinogenesis; Aristolochic Acids; DNA, Neoplasm; krysa rodu Rattus; Carcinogenesis; kyseliny aristolochové; Animals; Carcinogens; karcinogeny; DNA Adducts; zvířata; Rats; karcinogeneze; Balkan endemic nephropathy